2013
DOI: 10.5296/jbls.v4i2.2895
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of Microwave Radiation On The Retina Of Mice Embryos

Abstract: The present investigation is concerned with the effect of mobile phone radiation on the development of mice embryos. The pregnant females were divided into 3 groups, the control group (GI) and 2 irradiated groups, 10 females each. The 2 nd group and 3 rd group were subjected to 950MHz at SAR=1W/kg and 1800MHz at SAR=1.6W/kg respectively from day 7 to day 14 of gestation for 2 hours/ day. The exposure to microwave caused fetal growth retardation in all irradiated groups. However, no morphological abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…A previous study reported a significant increase in body weight and length at the 10th day, which could not be sustained at day 14 using 900-1800 MHz electromagnetic waves and ringing 4 times for 15 minutes/day [12]. However, a study by Amer and coworker described a decreased fetal weight in intrauterine exposure of rat and mouse animal models exposed to EMR ranging from 27.12 to 2450 MHz [14].…”
Section: Discussionmentioning
confidence: 97%
“…A previous study reported a significant increase in body weight and length at the 10th day, which could not be sustained at day 14 using 900-1800 MHz electromagnetic waves and ringing 4 times for 15 minutes/day [12]. However, a study by Amer and coworker described a decreased fetal weight in intrauterine exposure of rat and mouse animal models exposed to EMR ranging from 27.12 to 2450 MHz [14].…”
Section: Discussionmentioning
confidence: 97%
“…RFR can accelerate or decrease cell proliferation, especially during embryonic development (Panagopoulos, 2011; Zareen et al., 2009). Mobile radiation at certain frequencies can inhibit growth (Amer et al., 2013; Marcickiewicz, 1986; O'Connor, 1999). Intrauterine RFR radiation from 27.12 to 2450 MHz lowered mice’ foetal weight and crown‐rump length (Bonhomme‐Faivre et al., 2003).…”
Section: Discussionmentioning
confidence: 99%
“…246In contrast,Amer FI et al (2013) found a reduction of body length after the exposure of pregnant mice to 950-1,800 MHz for 2 h/day for 8 consecutive days from day 7 to 14 of gestation at SAR of 1-1.6 W/kg.…”
mentioning
confidence: 91%